Efeito do foco de atenção na aprendizagem de uma habilidade da ginástica - Giovanna Rodrigues Silva (2018)
The studies about focus of attention showed that concentrating in environmental aspects (external focus) is beneficial to the learning of a new motor skill. However, a few studies have investigated the effectiveness of the focus of attention in learning motor skills in which the goal is specifically the pattern of execution. In addition, the studies do not present measures that differ the performance in the task and the changes in the processes underlying the execution, such as the generalized motor program (GMP) and the parameters of the skill. The purpose of this study was to investigate the effect of focus of attention on learning a gymnastics skill - a Turn. This question investigated with a sample of 21 adult volunteers of both sexes, naive on the task. All the volunteers performed a pre-test, which consisted of executing 10 turns. The official scoring code of the modality was used to evaluate the performance and to counterbalance the groups - internal focus (IF) and external focus (EF). In addition, inertial sensors for motion analysis were use. During the acquisition phase, 150 trials performed in three practice sessions and the volunteers were question about their adherence to the instructed focus of attention. The retention, which consisted of executing 10 turns, performed 48 hours after the end of the acquisition phase. For analysis of the scoring code, GMP and parameters mixed ANOVAs two way were conduct. The results showed that both EF and IF promoted changes from the pre-test to retention test, however no differences between the groups were detected. In conclusion, concentrating in environmental aspects (EF) does not promote greater benefits for learning of this skill, as expected. However, it is important to take into account the subjects’ commitment to the instruction given initially and their strategies chosen throughout the acquisition phase to direct the attention.